فاعلیة تطبیقات الهواتف الذکیة لتعلم الجوانب العلمیة لتصنیف دیوى العشرى :دراسة تجریبیة على طلاب قسم المکتبات جامعة کفر الشیخ - د. عماد عبد الستار زیدان (المجلة الدولية لعلوم المكتبات والمعلومات)
The study contributes to shedding light on how to take advantage of whatwe carry in our hands of phones in making a quantum leap in the field ofeducation where the problem of study is clear from the non-use of smart phonesfor educational purposes in a large extent despite the widespread use and cheapprice and make available among university students and use only for purposesTraditional calls such as calling and sending messages,Its importance derives from the general direction of the state towards thedevelopment of education and the use of modern technology in education, andthe recommendations of many conferences on the importance of mobile learning,And to seek to verify the following assumptions : the existence of positiveattitudes for students towards learning using mobile phone, there are differencesof statistical significance between the average score of students of theexperimental group and the control group in the test achievement for the benefitof the experimental group, The study identified its tools in the scale of the trendtoward mobile education, and the application of mobile education designed by theresearcher to conduct this experiment, And achievement test ,The study was applied to a sample of second-year students in theDepartment of Libraries and Information University of Kafr El-Sheikh and wasdivided into two groups (experimental and control) ,The study found that 72% ofthe students have a positive trend towards learning mobile phone classification,which is high, and that learning mobile phone classification helps to increase therate of achievement study by 60%, The study concluded that the decisions of thelibrary and information sections should include a curriculum for programmingeducational applications for mobile phones and use of educational mobileapplications in distance education, continuing education and in-service trainingprograms